Preliminary Cytotoxic Study of Some Novel Furo-2-quinolone Compounds - Nohad A.AlOmari; Adnan O. Omar; Iklas M. Taher (College of Pharmacy University of Baghdad, 2017)
In this research, new series of Furo-2-quinolone [FQ] compounds have been synthesized. These novel [FQ] compounds were prepared from coumarin derivatives (Furocoumarins: psoralen and isopsoralen).Identifications of these FQ compounds were performed by using infrared spectrum (I.R), Ultraviolet spectrum (U.V) and Nuclear Magnetic Resonance spectrum (H1-NMR) besides some physical data. The cytotoxic screening involves ;using HEP-2 cell line which gave differential responses against tested compounds : 4,6 Dimethyl furo[2, 3-g] coumarin (C1), 1-(2`, 4`, Dimethoxy benzylideneimino)-2,6-dimethyl Furo [2, 3-g] quinoline-2-one (C3) and the angular psoralen of the same derivative with the chemical name; 1-(2`,4`-Dimethoxybenzylidenimine)-4,8,9-trimethyl furo[3,2-h] quinoline-2-one (C3A).These preliminary studies using different cell lines in addition to full cytotoxic screening may facilitate generation of better structural activity relationship and then shed the light for new lead promising anticancer compounds. Keyword: Coumarin, Angelicin, HEP-2 Cell line, cytotoxicity,